Attributing Legal Responsibility for Deepfake Pornography Generated by Artificial Intelligence: A Juridical Analysis - Dian Ningtias, Ayu; Nabilah, Wardatun; Ardiansyah, Diyan (Universitas Islam Lamongan, 2025)
The development of artificial intelligence technology has brought about major transformations in various fields, including in the digital media sector. One form of innovation that has emerged is deepfake technology. Although useful in some positive contexts, this technology has also been misused, especially in the form of pornographic deepfakes, namely the creation and distribution of fake pornographic content by displaying someone's face without permission. This phenomenon raises serious problems because it not only violates the right to privacy and individual dignity, but also has psychological and social impacts on victims. Although Indonesia does not yet have regulations that specifically regulate deepfakes, perpetrators can still be charged using the provisions of the Electronic Information and Transactions Law (UU ITE), the Pornography Law, and the Criminal Code (KUHP). However, the existing legal framework has not been fully able to answer the challenges of digital crime that continues to grow. Therefore, a more comprehensive and adaptive regulatory update is needed, as well as a strong legal protection mechanism for victims, to ensure legal justice in the increasingly complex digital era.